2020
DOI: 10.3390/app10217420
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in Milk and Dairy Products: Occurrence and Exposure Assessment for the Serbian Population

Abstract: The main objective of this study was to assess the exposure associated with aflatoxin M1 (AFM1) of the adult population in Serbia from consumption of milk and dairy products. This assessment was performed using concentration values of AFM1 in raw milk (385 samples) and dairy products (556 samples) based on the analyses conducted in the period between 2015 and 2018. In parallel, a dairy products consumption survey was completed during 2018 based on ‘one-day’ and ‘seven-day’ recall methods. In order to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The exposure of Serbia's adult population to AFM 1 from milk and dairy product consumption in 2015-2018 was examined by Djekic, et al [64] and confirmed the previous data. In fact, these authors showed a moderate exposure risk compared with similarly managed studies worldwide, but the research underlined the importance of promoting continuous monitoring of feed and dairy supply chains and providing exposure assessment updates, with the exposure variable depending on the monitoring year.…”
Section: Impact On Aspergillus Flavus and Aflatoxin Contaminationsupporting
confidence: 57%
“…The exposure of Serbia's adult population to AFM 1 from milk and dairy product consumption in 2015-2018 was examined by Djekic, et al [64] and confirmed the previous data. In fact, these authors showed a moderate exposure risk compared with similarly managed studies worldwide, but the research underlined the importance of promoting continuous monitoring of feed and dairy supply chains and providing exposure assessment updates, with the exposure variable depending on the monitoring year.…”
Section: Impact On Aspergillus Flavus and Aflatoxin Contaminationsupporting
confidence: 57%
“…The average bw of the interviewees was 73.36 kg, which is in line with the EFSA recommendation that the average bw of an adult European citizen is around 70 kg (EFSA, 2012a). One‐third of the interviewees were overweight with BMI >24.9, which coincides with the results of a study on the consumption of dairy products in Serbia during 2020 (Djekic et al ., 2020). Data from a national survey indicated that half of the population (54.5%) in Serbia during 2006 had a BMI above 24.9 (out of a total of 19 796 participants) (Grujic et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The fitting analysis showed normal distribution for bw and positively skewed distributions of daily/weekly intake of EEBP. Based on the distribution results, all data were randomised 100 000 times to perform Monte Carlo simulation, and EDIs were calculated (Djekic et al ., 2020). Exposure calculation was based on the mean value of all toxic elements (Table 4) since, over time, it is expected that an individual will be exposed to this concentration in EEBP (FAO/WHO, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In Serbia during the period 2015-2018, 46.2% of raw milk samples exceeded the EU MRL, with the highest frequency of 65.4% and maximal mean level of 220 ng/kg in autumn [43]. Another study conducted in Serbia in 2015-2016 also showed that 30% samples exceeded the EU MRL, and in relation to the frequency of contamination during the seasons, those two years showed significant differences, i.e., the highest frequency in 2015 was determined in autumn (47%) and summer (22%) while in 2016 the highest was in winter (52.7%) and spring (33%) [44].…”
Section: Occurrence Of Afm 1 In Milkmentioning
confidence: 98%